A national survey of career development according to gender and subspecialties among cardiologists in Japan - Mai Shimbo; Atsuko Nakayama; Noriko Fukue; Fumie Nishizaki; Chisa Matsumoto; Satsuki Noma; Satoko Ohno-Urabe; Chizuko A. Kamiya; Sachiko Kanki; Tomomi Ide; Hideo Izawa; Tatsunori Taniguchi; et al. (PLoS ONE, 2025)
Background Training opportunities, work satisfaction, and the factors that influence them according to gender and subspecialties are understudied among Japanese cardiologists. Methods We investigated the career development of Japanese cardiologists with an e-mail questionnaire. Feelings of inequality in training opportunities, work dissatisfaction, and reasons were assessed by examining the cardiologists’ gender and invasiveness of subspecialties. Results Responses were received from 2,566 cardiologists. Female cardiologists were underrepresented in invasive subspecialties compared to males (14.2% vs. 85.8%, p<0.0001). In both invasive and non-invasive subspecialties, female cardiologists felt more inequality in training opportunities than males (invasive: 50.0% vs. 36.2%, non-invasive: 41.6% vs. 30.9%, p<0.001, respectively) and were less satisfied with their work (invasive: 26.0% vs. 18.3%, non-invasive: 24.7% vs. 14.7%, p = 0.001, respectively). Although female cardiologists in invasive subspecialties did not feel significantly more inequal and dissatisfied than those in non-invasive subspecialties (p = 0.063 and p = 0.758, respectively), male cardiologists in invasive subspecialties felt more inequal and dissatisfied than those in non-invasive subspecialties (p = 0.015 and p = 0.040, respectively). Female cardiologists were more influenced by gender bias and family issues for inequality in training opportunities (p = 0.0001, respectively), whereas male cardiologists were likely to be affected by specifications of belonging hospitals. Both genders felt dissatisfied when their expectations were unmet and they were overworked. Conclusions Female cardiologists felt more inequality regarding training opportunities and dissatisfaction with career development than male cardiologists in both the invasive and non-invasive subspecialties. Diversity support is warranted for achieving satisfying career course regardless of gender and subspecialty.